Magi : the labyrinth of magic. 34 - Otaka, Shinobu; Werry, John (Translator) (VIZ Media, LLC, 2019)
"Having seized the Sacred Palace, Sinbad rewrites the world's Rukh and thus the world's fate. Alibaba, Aladdin and Morgiana decide that they must take matters into their own hands. With Hakuryu and Judar's help, they head for the Sacred Palace, where Sinbad awaits..."--Page [4] of cover.